2015
DOI: 10.1155/2015/316351
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Immunosuppressed IL-22 in Patients with Immune Thrombocytopenia via Soluble Cellular Factors

Abstract: Mesenchymal stem cells are immunoregulation cells. IL-22 plays an important role in the pathogenesis of immune thrombocytopenia. However, the effects of mesenchymal stem cells on IL-22 production in patients with immune thrombocytopenia remain unclear. Flow cytometry analyzed immunophenotypes of mesenchymal stem cells; differentiation of mesenchymal stem cells was observed by oil red O and Alizarin red S staining; cell proliferation suppression was measured with MTS; IL-22 levels of cell-free supernatants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Non-classical subsets of monocytes were found to be prominently elevated in patients with active ITP, contributing to the proliferation of platelet-reactive T cells and the production of interferon gamma [45]. Intermediate subsets of monocytes were also found to be increased, leading to the higher levels of tumor necrosis factor (TNF)-α and interleukin (IL)-1β, in negative correlation with platelet counts [42]. A recent publication showed that CD16+ monocytes could promote the development of Th1 cells, but inhibited the proliferation of Tregs and IL-17(+) Th cells, resulting in the imbalance of Th subsets and further contributing to the pathogenesis of ITP [46].…”
Section: Discussionmentioning
confidence: 99%
“…Non-classical subsets of monocytes were found to be prominently elevated in patients with active ITP, contributing to the proliferation of platelet-reactive T cells and the production of interferon gamma [45]. Intermediate subsets of monocytes were also found to be increased, leading to the higher levels of tumor necrosis factor (TNF)-α and interleukin (IL)-1β, in negative correlation with platelet counts [42]. A recent publication showed that CD16+ monocytes could promote the development of Th1 cells, but inhibited the proliferation of Tregs and IL-17(+) Th cells, resulting in the imbalance of Th subsets and further contributing to the pathogenesis of ITP [46].…”
Section: Discussionmentioning
confidence: 99%
“…3 In previous studies, alizarin has been used for staining and has been widely used in experiments on osteoporosis, bone marrow growth, and calcium deposits in the skeletal and vascular systems. [4][5][6][7][8][9][10] In addition to being a dye, alizarin has unexplained biological activities. The formation of biofilms and hyphal growth in Candida albicans is inhibited by alizarin.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, MSCs from bone marrow or adipose origin exhibited immunosuppressive effects and showed a concentration dependence. Clonal proliferation of lymphocytes can be found in ITP patients, but MSCs could inhibit the proliferation and co-stimulatory molecules CD40L and CD80 expression of these lymphocytes in vitro, especially for CD4 + T and CD19 + B cells [ 35 ]. In addition, MSCs can regulate the Th1/Th2 cell balance and promote Tregs, as shown by suppressing Th1-type cytokines, such as IFN-γ and TNF-α, and enhancing Th2-type cytokines, such as IL-4, ultimately restoring immune tolerance and alleviating ITP [ 36 ].…”
Section: Therapeutic Contribution Of Mscs In Itpmentioning
confidence: 99%